2011
DOI: 10.1210/en.2010-0674
|View full text |Cite
|
Sign up to set email alerts
|

Antiadipogenic Effects of the Mineralocorticoid Receptor Antagonist Drospirenone: Potential Implications for the Treatment of Metabolic Syndrome

Abstract: The mineralocorticoid receptor (MR) mediates aldosterone- and glucocorticoid-induced adipocyte differentiation. Drospirenone (DRSP) is a potent synthetic antimineralocorticoid with progestogenic and antiandrogenic properties, which is widely used for contraception and hormone replacement therapy. We investigated its potential role on adipocyte differentiation. The effects of DRSP were studied in murine preadipocyte cell lines and primary cultures of human preadipocytes. Differentiation markers and mechanisms u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
2
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(88 citation statements)
references
References 41 publications
3
74
2
9
Order By: Relevance
“…Thereby, DRSP may display favorable metabolic effects in women, in adequate combination with estrogens, to prevent excessive adipose tissue deposition and its related cardiometabolic complications (75).…”
Section: Medical Intervention In Pcosmentioning
confidence: 99%
“…Thereby, DRSP may display favorable metabolic effects in women, in adequate combination with estrogens, to prevent excessive adipose tissue deposition and its related cardiometabolic complications (75).…”
Section: Medical Intervention In Pcosmentioning
confidence: 99%
“…Other studies evidenced that GR has a more prevalent role, compared with MR, in promoting the maturation of preadipocytes (Lee & Fried 2014a). However, divergent reports showed that MR inhibition blocked the adipogenesis in vitro, whereas downregulation of GR did not (Caprio et al 2007(Caprio et al , 2011. Besides their effects on adipocytes growth, glucocorticoids play a well-known anti-inflammatory role, limiting the obesity-induced inflammation in adipose tissue (Fried et al 1998, Patsouris et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Either knockdown or pharmacological blockade of MR inhibits adipogenesis in 3T3L1 cultures (Caprio et al 2007(Caprio et al , 2011, revealing an important role for this transcription factor in adipose tissue physiology and pathophysiology. Pharmacological MR antagonism has been shown to counteract dysfunctional metabolism of adipose tissue (Guo et al 2008, Hirata et al 2009, Wada et al 2010.…”
Section: Introductionmentioning
confidence: 99%